Menolak Mafia Peradilan: Menjaga Integritas Hakim-Menyelaraskan Perbuatan Dan Nuraninya - Suparman, Eman, Prof. (Jurnal Hukum & Pembangunan, 2017)
The terminology is not only just a figment or slander. In fact, its present has been confirmed by the establishment of the Judicial Mafia Eradication Task Force by President Susilo Bambang Yudhoyono. Lately, some important events have occurred in Indonesian judiciary organs. The welfare improvement program for judges, which was manifested by the Judicial Commission, Government and Parliament of the Republic of Indonesia in the form of increased allowances of judges, has not been able to significantly erode the corrupt behavior of some unscrupulousgreedy judges.Therefore, in order to respond to the objective conditions that occur lately, the President of the Republic of Indonesia has to 9establish Policy Package on Law Reformation for judicial authorities in Supreme Court.